Association of barnacles with snakes and worms - Willey, Arthur (Spolia Zeylanica, 1910)
Begins: "The object of this note is to present to the readers of this journal a picture showing a group of barnacles belonging to two species attached by their stalks to the flattened tail of a sea-snake, Hydrus platurus [= Pelamis platura]. The attachment of barnacles to the skin of sea-snakes has long been known, and was of course mentioned repeatedly by Darwin in his "Monograph of the Cirripedes," but a conspicuous example like the one here figured is not so commonly met with in Ceylon." Later: "In August , 1907 , and December, 1909, Lepas-logs were brought to me at the Museum, upon which I found numbers of these two species, Amphinome rostrata and Hipponoe gaudichaudi, not recorded from Ceylon …"
World Polychaeta Database (WPolyDb)